Profile of Women with Late Menstrual Period - Eka R. Gunardi (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To know the profile of women with late menstrual period in Raden Saleh Clinic Jakarta in 2008 - 2011. Method: This was a descriptive study with 400 samples from medical records, choosen by random sampling. The data of age, education, occupation, marital status, residence, religion, parity, age of the youngest kid, cause of pregnancy, attempt to abort, referral, reason to end pregnancy, and contraceptive method post menstrual induction were collected. Result: The majority of women who underwent menstrual induction were 18 - 35 years old (57.25%), followed by women aged more than 35 years old (40.5%) and below 18 years old (2.25%). Most women were graduated from middle school (51.25%), unemployed (65.25%), and married (90.8%). They mostly came from Jakarta and satellite cities such as Depok, Bogor, Tangerang, and Bekasi, which accounted for 88% clients. Most of them have two children (32.3%) with the youngest kid aged more than 12 months old (60%). The causes of pregnancy were neglecting to use contraception (87.5%), failure of contraception (12%), and sexual assault (0.5%). As much as 44% of the clients had tried to end the pregnancy before they came to Raden Saleh Clinic and 87.5% of all 400 women came without referral. The most common reason was having had enough children in 74% of the women to end the pregnancy, followed by 12.25% of clients who wanted to pursue higher education. After treated by menstrual induction, 75.8% of them used IUD as contraception. Conclusion: Our data showed that mean age of women who were underwent menstrual induction is 32.94 Â± 0.35 years old and the main reason to do menstrual induction in this research is the consideration of having enough children. [Indones J Obstet Gynecol 2013; 37-1: 41-5] Keywords: age, contraception, late menstrual period, menstrual induction